THE LEGALITY OF SURROGATE MOTHERS FROM THE ISLAMIC LAW PERSPECTIVE - Nurul Mujahidah; Sabri Samin; Syatirah Djalaluddin; M. Nur Hidayatullah (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aimed to analyze the legal standing of surrogate mothers from the Islamic law perspective. This study employed library research with a shar'i normative approach. The data were collected through documents related to the surrogate mother, both from books, texts (Qur'an and Sunnah), and scholars’ opinions who discussed the implementation of a surrogate mother. Surrogate mother was one of the efforts made by a married couple to produce descendants. The results of this study indicated that the law of having descendants in a marriage was not something included in the dharuriyyah part or must exist. Additionally, the legal consequences of implementing a surrogate mother would have an impact on the child born, both from the status of the child born from the surrogate mother including legitimate child or illegitimate child, who was the mother or the mother status of children born from the surrogate mother, and the rights inheritance of children born from surrogate mother. Therefore, based on the Qur'an and Sunnah, individual and group scholars' opinions stated that the legal standing of surrogate mothers in Islam was unlawful.